Preprotein signature for full susceptibility to the co‐translational translocation inhibitor cyclotriazadisulfonamide. (25th November 2019) - Van Puyenbroeck, Victor; Pauwels, Eva; Provinciael, Becky; Bell, Thomas W.; Schols, Dominique; Kalies, Kai‐Uwe; Hartmann, Enno; Vermeire, Kurt
Abstract: Cyclotriazadisulfonamide (CADA) inhibits the co‐translational translocation of human CD4 (huCD4) into the endoplasmic reticulum lumen in a signal peptide (SP)‐dependent way. We propose that CADA binds the nascent huCD4 SP in a folded conformation within the translocon resembling a normally transitory state during translocation. Here, we used alanine scanning on the huCD4 SP to identify the signature for full susceptibility to CADA. In accordance with our previous work, we demonstrate that residues in the vicinity of the hydrophobic h‐region are critical for sensitivity to CADA. In particular, exchanging Gln‐15, Val‐17 or Pro‐20 in the huCD4 SP for Ala resulted in a resistant phenotype. Together with positively charged residues at the N‐terminal portion of the mature protein, these residues mediate full susceptibility to the co‐translational translocation inhibitory activity of CADA towards huCD4. In addition, sensitivity to CADA is inversely related to hydrophobicity in the huCD4 SP. In vitro translocation experiments confirmed that the general hydrophobicity of the h‐domain and positive charges in the mature protein are key elements that affect both the translocation efficiency of huCD4 and the sensitivity towards CADA. Besides these two general SP parameters that determine the functionality of the signal sequence, unique amino acid pairs (L14/Q15 and L19/P20) in the SP hydrophobic core add specificity to the sensitivity signature for a co‐translational translocation inhibitor. Abstract : Alanine scanning on the huCD4 signal peptide revealed that the general hydrophobicity of the hydrophobic (h)‐domain of the signal peptide (SP) and positive charges in the mature protein are key elements that affect both the translocation efficiency of huCD4 and the sensitivity toward the small molecule translocation inhibitor cyclotriazadisulfonamide (CADA). In addition, unique amino acid pairs (L14/Q15 and L19/P20) in the SP hydrophobic core add specificity to the sensitivity signature for CADA.